2012
DOI: 10.1111/j.1524-4725.2011.02258.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Second-Intention Healing in the Management of Defects on the Dorsal Surface of the Hands and Fingers after Mohs Micrographic Surgery

Abstract: Second-intention healing is an effective option for repairing defects on the dorsum of the hand and fingers. Large defect size is not a contraindication for second-intention healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
(40 reference statements)
3
17
0
2
Order By: Relevance
“…Complications such as postoperative pain, bleeding and infection were uncommon. This is in keeping with the low complication rates reported with secondary intention healing at other sites . There were no organisms isolated from the wound swabs taken from the two patients who developed postoperative erythema at the wound edges accompanied by pain.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Complications such as postoperative pain, bleeding and infection were uncommon. This is in keeping with the low complication rates reported with secondary intention healing at other sites . There were no organisms isolated from the wound swabs taken from the two patients who developed postoperative erythema at the wound edges accompanied by pain.…”
Section: Discussionsupporting
confidence: 81%
“…Secondary intention healing may also be adopted for wounds at body sites other than the head and neck. Its usefulness has been documented for wounds on the trunk and limbs, legs, plantar surface of the feet, nipple–areola complex, tips of the digits, and the dorsa of the hands and fingers …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MMS should be considered the ideal therapeutical method for such a location. In cases of a large surgical defect in the distal phalanx of a finger, cutaneous flaps or grafts could be very complex, and secondary‐intention healing appears as an interesting alternative . In addition, the use of hydrocolloid dressings would favour adequate healing and lead to a better aesthetic result…”
Section: Discussionmentioning
confidence: 99%
“…Mohs micrographic surgery (MMS) has been proposed as the best therapeutical option when there is no bone compromise because it allows the preservation of healthy tissue and increases the chances of success . After removing the tumour, the surgical defect could be resolved by flaps or grafts; however, sometimes these options are not convenient, and the secondary‐intention method could be the best option …”
Section: Introductionmentioning
confidence: 99%
“…A case report also showed that SIH can be used for defects on the dorsum of the hands and fingers with preservation of function so long as the defects did not traverse joints or expose tendons. 12 It should be noted that scar tissue is relatively hypopigmented and avascular and will contrast sharply against skin that is darkly pigmented or has many telangiectasias. Additionally, SIH should be avoided near free anatomic margins, which can be distorted as the wound contracts.…”
Section: When To Considermentioning
confidence: 99%